THE THEORETICAL SIGNIFICANCE OF THE DEVELOPMENT OF THE PROFESSIONAL COMPETENCE OF THE TUTOR OF A SPECIAL EDUCATIONAL INSTITUTION - Makhmudova Madinakhan (Galaxy International Interdisciplinary Research Journal, 2023)
The article describes the theoretical importance of the development of the professional competence of a teacher of a special education institution and the social and professional competences of a special education teacher that allow the cognitive development of children.